Preparation method of lightweight alkali-activated biomass power plant ash-blast furnace slag composite cementing material
By using the ash and blast furnace slag of the biomass power plant, and combined with the design of the alkali stimulus and foaming agent, the light-alkaline-based biomass power plant ash-blast furnace slag composite gel material is used to solve the existing cement base composite gel material The problem of resource consumption and environmental pollution during the production process realizes high -performance green building materials.
Patent Information
- Application Number
- CN202411501248.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-21
AI Technical Summary
The existing cement-based composite cementitious materials need to consume a large amount of fuel and electricity during the production process, and emit a large amount of greenhouse gases and pollutants, which poses harm to the environment and human health.
Using biomass power plant ash and blast furnace slag as raw materials, through the design of alkali activators and foaming agents, a light alkali-activated biomass power plant ash-blast furnace slag composite cementitious material is prepared to realize the reuse of resources and reduce the cost of the production process. Resource consumption and environmental impact.
The prepared composite cementitious material has a compressive strength of up to 2.25MPa at 28 days of age, low thermal conductivity, light weight, and good thermal insulation. It is a potential green building material.
Smart Images

Figure CN119330617A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomass power plant ash, in particular to a method for preparing a light alkali-activated biomass power plant ash-blast furnace slag composite cementitious material. Background Art
[0002] As the world continues to advance towards the goal of achieving carbon neutrality, biomass energy, as a renewable energy source, plays an important role in reducing carbon emissions. As a byproduct of biomass power generation, the resource utilization of biomass power plant ash (BPPA) has become an important direction for promoting sustainable development.
[0003] After searching, the patent with application number CN202410569188.5 discloses a composite cement-based cementitious material and a preparation method thereof, which relates to the field of grouting reinforcement technology. The composite cement-based cementitious material of the present invention includes component A, component B and water, wherein component A includes cement and activated lithium slag, and component B includes water reducer, water glass, and isomeric alcohol polyoxyethylene ether. The present invention significantly reduces the activation temperature and activation time of lithium slag by adding an activation aid, reduces the preparation cost of the product, and improves the stability and processing performance of the cementitious material by using activated lithium slag and isomeric alcohol polyoxyethylene ether. The composite cement-based cementitious material of the present invention can achieve a higher cement replacement amount, which not only reduces the discharge of industrial waste, but also reduces the impact on the environment. At the same time, no complicated equipment or technology is required in the product preparation process, and it is easy to operate on site. While improving the working performance and mechanical properties of the cementitious material, it reduces the production cost and is suitable for large-scale application.
[0004] The current cement-based composite cementitious materials require grinding, high-temperature calcination and other processes during the production process, all of which consume a lot of fuel and electricity. The production of each ton of cement clinker consumes approximately 1.2 tons of limestone, 0.3 tons of clay, 80 kilograms of gypsum, 110 kilograms of coal fuel and 110 kWh of electricity resources. The high-temperature treatment links in the cement production process, such as the operation of rotary kilns and pre-decomposition kilns, all need to maintain a high temperature state, which also consumes a lot of energy; secondly, cement production will emit a large amount of greenhouse gases and pollutants such as carbon dioxide, sulfur dioxide, and nitrogen oxides, which are harmful to the environment and human health; therefore, we need to propose a method for preparing a light alkali-activated biomass power plant ash-blast furnace slag composite cementitious material, using biomass power plant ash and blast furnace slag, the by-products of biomass power generation, as raw materials to prepare composite cementitious materials, so as to achieve resource reuse, promote sustainable development, and reduce the impact on the environment. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a light alkali-activated biomass power plant ash-blast furnace slag composite cementitious material. Through the design of biomass power plant ash, blast furnace slag, alkali activator and foaming agent (Al powder), biomass power plant ash and blast furnace slag, which are byproducts of biomass power generation, are used as raw materials to achieve resource reuse, promote sustainable development, reduce resource consumption in the production process of composite cementitious materials, and reduce impact on the environment. The prepared composite cementitious material has a compressive strength of up to 2.25MPa at 28 days of age, a thermal conductivity as low as 0.08162W / (m·K), and has the characteristics of light weight (porous) and good thermal insulation, and is a potential green building material.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material, comprising the following steps:
[0007] S1. Drying raw materials: removing moisture from biomass power plant ash and blast furnace slag;
[0008] S2. preparing an alkaline activator solution: used to activate the activity of biomass power plant ash and blast furnace slag;
[0009] S3. Weighing raw materials: according to the ratio of biomass power plant ash and blast furnace slag, use accurate weighing equipment to weigh biomass power plant ash, blast furnace slag and alkali activator;
[0010] S4, preparing a foaming agent suspension: used to form pores in the material and reduce the density of the material;
[0011] S5, dry material mixing: mixing the biomass power plant ash and blast furnace slag and stirring evenly;
[0012] S6, slurry preparation: adding an alkali activator solution to the uniformly mixed biomass power plant ash and blast furnace slag, and stirring and mixing to form a uniform slurry;
[0013] S7, foaming treatment: adding a foaming agent suspension to the prepared uniform slurry, and stirring at high speed for 10 seconds to foam the slurry;
[0014] S8. Casting test blocks: Pour the foamed slurry into the test mold immediately, vibrate it for 5 seconds using a cement vibrating table, and cast it into test blocks;
[0015] S9. Curing test blocks: Transfer the cast test blocks to a standard curing room to allow the materials in the test blocks to fully react and solidify to form composite cementitious materials;
[0016] S10. Basic performance test: The compressive strength test, splitting tensile strength test, thermal conductivity density test and dry density test are carried out on the cured test blocks to comprehensively evaluate the performance of the prepared composite cementitious material.
[0017] Preferably, in step S1, when drying the raw materials, the biomass power plant ash and blast furnace slag are placed in an oven at a temperature of 105 degrees Celsius and dried for 48 hours to ensure that the water content in the biomass power plant ash and blast furnace slag has no effect on subsequent reactions.
[0018] Preferably, in step S2, when preparing the alkaline activator solution, zero-hydrate sodium metasilicate and sodium hydroxide are weighed, and the mass ratio of zero-hydrate sodium metasilicate to sodium hydroxide is 100:57.04, and the two are mixed and blended to obtain an alkaline activator solution with a modulus of 0.5;
[0019] Weigh zero hydrate sodium metasilicate and sodium hydroxide again, and the mass ratio of zero hydrate sodium metasilicate to sodium hydroxide is 100:45.89, mix the two and prepare an alkaline activator solution with a modulus of 0.55;
[0020] The prepared alkaline activator solution is placed at room temperature to cool, and then sealed and stored after cooling to room temperature to prevent the solution from absorbing carbon dioxide and moisture.
[0021] Preferably, in step S3, the weighing equipment is any one of an electronic balance and a platform scale, and before weighing the raw materials, the weighing equipment is cleaned and dried to prevent impurities or moisture from affecting the weighing results. After weighing the biomass power plant ash and blast furnace slag, the weighing equipment is cleaned, and then zero-water sodium metasilicate and sodium hydroxide are weighed to avoid cross infection.
[0022] Preferably, in step S4, 5% of the mass of the aqueous solution corresponding to the water-binder ratio in the mix ratio is taken out and mixed with Al powder to prepare a foaming agent suspension. During the mixing process, a stirrer or a stirring rod is used to fully stir the aqueous solution and the Al powder so that the Al powder is fully dissolved in the aqueous solution to form a stable foaming agent suspension.
[0023] Preferably, in step S5, when mixing biomass power plant ash and blast furnace slag, the dried biomass power plant ash and blast furnace slag are first added to a stirring pot for pre-mixing, and then the stirring equipment is started for formal stirring, and low-speed stirring is started for 5 minutes to ensure that the two are evenly mixed, thereby laying a good foundation for subsequent slurry preparation.
[0024] Preferably, in step S6, the alkaline activator solution stored at room temperature is added to the mixed material of biomass power plant ash and blast furnace slag, first stirred at a low speed for 2 minutes, then stirred at a medium speed for 3 minutes, and after stirring, the slurry is left to stand for 20 minutes.
[0025] Preferably, in step S7, the foaming agent suspension is slowly added to the slurry and stirred sufficiently to gradually release the gas in the foaming agent suspension, and the gas is mixed with the slurry to form bubbles.
[0026] Preferably, in step S8, the slurry of mixed Al powder is evenly distributed in the test mold, which is conducive to the uniformity of foaming. After the foaming process is completed, the plastic wrap is promptly covered to prevent water loss;
[0027] In step S9, the temperature of the standard curing room is controlled at 25±1 degrees Celsius and the humidity is controlled at 95±1%. The test blocks are demolded after one day of curing. The demolded test blocks need to be wrapped with plastic wrap to ensure that the test blocks are not in contact with the external environment.
[0028] Preferably, in step S10:
[0029] Compressive strength test: Before the test, each group of test blocks must be flat and the mass difference between the two tests before and after drying should be no more than 1g, 4 hours apart. The test should be carried out at a pressure speed of 2.5kN / s.
[0030] Splitting tensile strength test: Use a non-standard test block of 100 mm and take the strength value after the size conversion coefficient. During the test, place a pad between the test block and the pressure plate, and ensure that the center line is aligned and vertical;
[0031] Thermal conductivity density measurement: The test uses a plate-shaped sample with a size of 300mm×300mm×30mm. The test block is pre-treated and dried at 105°C to constant weight. The test block is then placed in standard laboratory air and continuously adjusted to balance with the indoor air.
[0032] Dry density determination: Before the determination, the biomass power plant ash-blast furnace slag composite cementitious material after standard curing is placed in an oven and dried to a constant mass state.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention adopts biomass power plant ash and blast furnace slag, alkali activator and foaming agent (Al powder), which are byproducts of biomass power generation, as raw materials, to achieve resource reuse, promote sustainable development, reduce resource consumption in the composite gelling production process, and reduce the impact on the environment.
[0035] 2. The composite cementitious material prepared by the present invention has a compressive strength of up to 2.25 MPa at 28 days of age, a thermal conductivity as low as 0.08162 W / (m·K), and has the characteristics of light weight (porous) and good thermal insulation, and is a potential green building material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a flowchart of the present invention;
[0037] Figure 2The bar graph is a graph of compressive strength and dry density (water-binder ratio is 0.650) of various mix ratios at different ages of the present invention;
[0038] Figure 3 The bar graph is a graph of the compressive strength and dry density (water-binder ratio is 0.675) of each mix ratio at different ages of the present invention;
[0039] Figure 4 The figure is a bar graph of splitting tensile strength and dry density (water-binder ratio is 0.650) of each mix ratio at different ages of the present invention;
[0040] Figure 5 It is a bar graph of splitting tensile strength and dry density (water-binder ratio is 0.675) of various mix ratios at different ages of the present invention. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] See also Figure 1-5 The present invention provides a technical solution: a method for preparing a light alkali-activated biomass power plant ash-blast furnace slag composite cementitious material, which combines biomass power plant ash with blast furnace slag and other materials through alkali activation technology to prepare a light cementitious material with excellent performance. The composite cementitious material prepared by this method mainly includes biomass power plant ash, blast furnace slag, alkali activator, foaming agent (aluminum powder) and water, and includes the following steps:
[0043] S1. Drying raw materials: removing moisture from biomass power plant ash and blast furnace slag;
[0044] In step S1, when drying the raw materials, the biomass power plant ash and blast furnace slag are placed in an oven at a temperature of 105 degrees Celsius for 48 hours to ensure that the water content in the biomass power plant ash and blast furnace slag has no effect on the subsequent reaction.
[0045] During the drying process, the temperature must be strictly controlled to avoid excessive temperature causing deterioration or burning of the raw materials, and the humidity of the raw materials must be monitored in real time to ensure that the required degree of drying is achieved.
[0046] S2. preparing an alkaline activator solution: used to activate the activity of biomass power plant ash and blast furnace slag;
[0047] In step S2, when preparing the alkaline activator solution, zero-hydrate sodium metasilicate and sodium hydroxide are weighed, and the mass ratio of zero-hydrate sodium metasilicate to sodium hydroxide is 100:57.04, and the two are mixed and blended to obtain an alkaline activator solution with a modulus of 0.5;
[0048] Weigh zero hydrate sodium metasilicate and sodium hydroxide again, and the mass ratio of zero hydrate sodium metasilicate to sodium hydroxide is 100:45.89, mix the two and prepare an alkaline activator solution with a modulus of 0.55;
[0049] The prepared alkaline activator solution is placed at room temperature to cool, and then sealed and stored after cooling to room temperature to prevent the solution from absorbing carbon dioxide and moisture.
[0050] S3. Weighing raw materials: according to the ratio of biomass power plant ash and blast furnace slag, use accurate weighing equipment to weigh biomass power plant ash, blast furnace slag and alkali activator;
[0051] The weighing of biomass power plant ash and blast furnace slag should refer to the predetermined mix ratio in mix ratio design table 1:
[0052] Mix design table 1
[0053]
[0054]
[0055] Alkali equivalent is equivalent to the amount of alkali added. Alkali equivalent is 1.5, which means the amount of alkali added is 1.5% of the total mass of biomass power plant ash and blast furnace slag. Aluminum powder is 0.1, which means the amount of aluminum powder added is 0.1% of the total mass of biomass power plant ash and blast furnace slag. wt / % represents mass percentage. In the above table, biomass power plant ash accounts for 35% of the raw material mass, and blast furnace slag accounts for 65% of the raw material mass. w / b is the water-binder ratio.
[0056] In step S3, the weighing equipment is selected from any one of an electronic balance and a platform scale, and before weighing the raw materials, the weighing equipment is cleaned and dried to prevent impurities or moisture from affecting the weighing results. After weighing the biomass power plant ash and blast furnace slag, the weighing equipment is cleaned, and then zero-water sodium metasilicate and sodium hydroxide are weighed to avoid cross infection.
[0057] If you use a container for weighing, you should first perform a tare operation, that is, weigh the weight of the container first, then subtract the weight of the container from the weighing result to get the net weight of the raw materials; slowly pour the raw materials into the weighing tool until the required weight is reached. During the weighing process, you should pay attention to the reading of the weighing tool to ensure the accuracy of the weighing results; after weighing, you should record the weighing results of the raw materials for subsequent calculations and proportioning.
[0058] S4, preparing a foaming agent suspension: used to form pores in the material and reduce the density of the material;
[0059] In step S4, 5% of the mass of the aqueous solution corresponding to the water-binder ratio (w / b) in the mix ratio is taken out and mixed with Al powder to prepare a foaming agent suspension. During the mixing process, a stirrer or a stirring rod is used to fully stir the aqueous solution and the Al powder so that the Al powder is fully dissolved in the aqueous solution to form a stable foaming agent suspension.
[0060] In addition, the concentration of the suspension can be adjusted by adding an appropriate amount of water as needed. Too high a concentration may cause uneven distribution of the foaming agent in the material, affecting the foaming effect; too low a concentration may not achieve the expected foaming amount.
[0061] It is worth noting that when preparing the foaming agent suspension, safety precautions should be taken, such as wearing protective equipment such as gloves and masks to avoid irritation and damage to the skin or respiratory tract caused by the foaming agent. The prepared foaming agent suspension should remain stable to avoid stratification and precipitation during the preparation process or storage. The preparation time of the foaming agent suspension should be controlled within a certain range to avoid prolonged stirring that may cause the foaming agent to decompose or fail.
[0062] S5, dry material mixing: mixing the biomass power plant ash and blast furnace slag and stirring evenly;
[0063] In step S5, when mixing the biomass power plant ash and blast furnace slag, first add the dried biomass power plant ash and blast furnace slag into the stirring pot for pre-mixing, and then start the stirring equipment for formal stirring, start low-speed stirring for 5 minutes to ensure that the two are evenly mixed, so as to lay a good foundation for the subsequent slurry preparation.
[0064] During the mixing process, the mixing situation should be observed at any time and appropriate adjustments should be made as needed. For example, if uneven mixing or lumps are found, the mixing time can be appropriately extended or the mixing intensity can be increased.
[0065] S6, slurry preparation: adding an alkali activator solution to the uniformly mixed biomass power plant ash and blast furnace slag, and stirring and mixing to form a uniform slurry;
[0066] In step S6, the alkaline activator solution stored at room temperature is added to the mixed material of biomass power plant ash and blast furnace slag, first stirred at a low speed for 2 minutes, then stirred at a medium speed for 3 minutes, and after stirring, the slurry is left to stand for 20 minutes.
[0067] During the stirring process, ensure that the alkaline activator solution can be evenly distributed in the dry material and fully activate the activity of the raw materials.
[0068] And, as needed, the consistency of the slurry can be adjusted by adding an appropriate amount of water. A slurry with too high a consistency may be difficult to pour and form, while a slurry with too low a consistency may affect the strength and stability of the material. Therefore, when adjusting the consistency, the optimal amount of water should be determined based on the requirements of the preparation process and the characteristics of the raw materials.
[0069] S7, foaming treatment: adding a foaming agent suspension to the prepared uniform slurry, and stirring at high speed for 10 seconds to foam the slurry;
[0070] In step S7, the foaming agent suspension is slowly added to the slurry and stirred sufficiently to gradually release the gas in the foaming agent suspension, and the gas is mixed with the slurry to form bubbles.
[0071] Furthermore, in some cases, air or other gases may be introduced to further enhance the foaming effect.
[0072] After the foaming process, key indicators such as the density, stability, and uniformity of the foam need to be evaluated, such as observing the appearance of the foam and measuring the density and stability of the foam.
[0073] S8. Casting test blocks: Pour the foamed slurry into the test mold immediately, vibrate it for 5 seconds using a cement vibrating table, and cast it into test blocks;
[0074] In step S8, the slurry of the mixed oil AI powder is evenly distributed in the test mold, which is conducive to the uniformity of foaming. After the foaming process is completed, the plastic wrap is promptly covered to prevent water loss;
[0075] Before pouring, the mold should be thoroughly cleaned to remove impurities and oil stains on the mold surface. This can ensure good contact between the test block and the mold and avoid damage or deformation of the test block during demoulding.
[0076] S9. Curing test blocks: Transfer the cast test blocks to a standard curing room to allow the materials in the test blocks to fully react and solidify to form composite cementitious materials;
[0077] In step S9, the temperature of the standard curing room is controlled at 25±1 degrees Celsius and the humidity is controlled at 95±1%. The test blocks are demolded after one day of curing. The demolded test blocks need to be wrapped with plastic wrap to ensure that the test blocks are not in contact with the external environment.
[0078] S10. Basic performance test: The compressive strength test, splitting tensile strength test, thermal conductivity density test and dry density test are carried out on the cured test blocks to comprehensively evaluate the performance of the prepared composite cementitious material.
[0079] It is worth noting that the compressive strength test and splitting tensile strength test refer to "Foamed Concrete" (JG / T266-2011) and "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019) respectively; the dry density determination refers to JC / T2357-2016 "Test Methods for Performance of Foamed Concrete Products" for testing; the thermal conductivity coefficient is determined in accordance with the "Transient Plane Heat Source Test Method for Thermal Conductivity and Thermal Diffusivity of Building Materials" (GB / T32064-2015).
[0080] In step S10:
[0081] Compressive strength test: Before the test, each group of test blocks must be flat and the mass difference between the two tests before and after drying should be no more than 1g, 4 hours apart. The test should be carried out at a pressure speed of 2.5kN / s.
[0082] Splitting tensile strength test: a non-standard test block of 100 mm was selected, and the strength value was converted by the size conversion coefficient. During the test, a pad was placed between the test block and the pressure plate, and the center line was aligned and vertical. During the test, the compressive strength of the cube was less than 30 MPa, so the loading speed was selected as 0.02 MPa / s.
[0083] Thermal conductivity density measurement: The test uses a plate-shaped sample with a size of 300mm×300mm×30mm. The test block is pre-treated and dried at 105°C to constant weight. The test block is then placed in standard laboratory air (296K±1K; 50%±10%RH) and continuously adjusted to balance with the indoor air.
[0084] Dry density determination: Before the determination, the biomass power plant ash-blast furnace slag composite cementitious material after standard curing is placed in an oven and dried to a constant mass state.
[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material, characterized in that: The following steps are involved: S1. Drying raw materials: removing moisture from biomass power plant ash and blast furnace slag; S2. preparing an alkaline activator solution: used to activate the activity of biomass power plant ash and blast furnace slag; S3. Weighing raw materials: according to the ratio of biomass power plant ash and blast furnace slag, use accurate weighing equipment to weigh biomass power plant ash, blast furnace slag and alkali activator; S4, preparing a foaming agent suspension: used to form pores in the material and reduce the density of the material; S5, dry material mixing: mixing the biomass power plant ash and blast furnace slag and stirring evenly; S6, slurry preparation: adding an alkali activator solution to the uniformly mixed biomass power plant ash and blast furnace slag, and stirring and mixing to form a uniform slurry; S7, foaming treatment: adding a foaming agent suspension to the prepared uniform slurry, and stirring at high speed for 10 seconds to foam the slurry; S8. Casting test blocks: Pour the foamed slurry into the test mold immediately, vibrate it for 5 seconds using a cement vibrating table, and cast it into test blocks; S9. Curing test blocks: Transfer the cast test blocks to a standard curing room to allow the materials in the test blocks to fully react and solidify to form composite cementitious materials; S10. Basic performance test: The compressive strength test, splitting tensile strength test, thermal conductivity density test and dry density test are carried out on the cured test blocks to comprehensively evaluate the performance of the prepared composite cementitious material.
2. The method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material according to claim 1, characterized in that: In step S1, when drying the raw materials, the biomass power plant ash and blast furnace slag are placed in an oven at a temperature of 105 degrees Celsius for 48 hours to ensure that the water content in the biomass power plant ash and blast furnace slag has no effect on the subsequent reaction.
3. The method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material according to claim 1, characterized in that: In step S2, when preparing the alkaline activator solution, zero-hydrate sodium metasilicate and sodium hydroxide are weighed, and the mass ratio of zero-hydrate sodium metasilicate to sodium hydroxide is 100:57.04, and the two are mixed and blended to obtain an alkaline activator solution with a modulus of 0.5; Weigh zero hydrate sodium metasilicate and sodium hydroxide again, and the mass ratio of zero hydrate sodium metasilicate to sodium hydroxide is 100:45.89, mix the two and prepare an alkaline activator solution with a modulus of 0.55; The prepared alkaline activator solution is placed at room temperature to cool, and then sealed and stored after cooling to room temperature to prevent the solution from absorbing carbon dioxide and moisture.
4. The method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material according to claim 1, characterized in that: In step S3, the weighing equipment is selected from any one of an electronic balance and a platform scale, and before weighing the raw materials, the weighing equipment is cleaned and dried to prevent impurities or moisture from affecting the weighing results. After weighing the biomass power plant ash and blast furnace slag, the weighing equipment is cleaned, and then zero-water sodium metasilicate and sodium hydroxide are weighed to avoid cross infection.
5. The method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material according to claim 1, characterized in that: In step S4, 5% of the mass of the aqueous solution corresponding to the water-binder ratio in the mix ratio is taken out and mixed with Al powder to prepare a foaming agent suspension. During the mixing process, a stirrer or a stirring rod is used to fully stir the aqueous solution and the Al powder so that the Al powder is fully dissolved in the aqueous solution to form a stable foaming agent suspension.
6. The method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material according to claim 1, characterized in that: In step S5, when mixing the biomass power plant ash and blast furnace slag, first add the dried biomass power plant ash and blast furnace slag into the stirring pot for pre-mixing, and then start the stirring equipment for formal stirring, start low-speed stirring for 5 minutes to ensure that the two are evenly mixed, so as to lay a good foundation for the subsequent slurry preparation.
7. The method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material according to claim 1, characterized in that: In step S6, the alkaline activator solution stored at room temperature is added to the mixed material of biomass power plant ash and blast furnace slag, first stirred at a low speed for 2 minutes, then stirred at a medium speed for 3 minutes, and after stirring, the slurry is left to stand for 20 minutes.
8. The method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material according to claim 1, characterized in that: In step S7, the foaming agent suspension is slowly added to the slurry and stirred sufficiently to gradually release the gas in the foaming agent suspension, and the gas is mixed with the slurry to form bubbles.
9. The method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material according to claim 1, characterized in that: In step S8, the slurry of mixed Al powder is evenly distributed in the test mold, which is conducive to the uniformity of foaming. After the foaming process is completed, the plastic wrap is promptly covered to prevent water loss; In step S9, the temperature of the standard curing room is controlled at 25±1 degrees Celsius and the humidity is controlled at 95±1%. The test blocks are demolded after one day of curing. The demolded test blocks need to be wrapped with plastic wrap to ensure that the test blocks are not in contact with the external environment.
10. The method for preparing a light alkali activated biomass power plant ash-blast furnace slag composite cementitious material according to claim 1, characterized in that: In step S10: Compressive strength test: Before the test, each group of test blocks must be flat and the mass difference between the two tests before and after drying should be no more than 1g, 4 hours apart. The test should be carried out at a pressure speed of 2.5kN / s. Splitting tensile strength test: Use a non-standard test block of 100 mm and take the strength value after the size conversion coefficient. During the test, place a pad between the test block and the pressure plate, and ensure that the center line is aligned and vertical; Thermal conductivity density measurement: The test uses a plate-shaped sample with a size of 300mm×300mm×30mm. The test block is pre-treated and dried at 105°C to constant weight. The test block is then placed in standard laboratory air and continuously adjusted to balance with the indoor air. Dry density determination: Before the determination, the biomass power plant ash-blast furnace slag composite cementitious material after standard curing is placed in an oven and dried to a constant mass state.
Citation Information
Patent Citations
Composite cement-based cementing material and preparation method thereof
CN118344117A
Cited By
All-solid-waste biomass ash-based light soil and preparation method thereof
CN119874314A
Industrial and agricultural solid waste-based carbon-sequestration thermal-insulation high-strength geopolymer material and preparation method thereof
CN121159162A